Gifted pupils’ learning experience in virtual laboratories - Kapıcı, Hasan Özgür; Coştu, Fatma (Journal of Turkish Science Education, 2024)
One of the main courses that have been affected by instructional technology is science education since the nature of topics covered by the science curriculum may require the usage of technology to teach them better. Based on this, the aim of the current study is to investigate the effects of virtual laboratories on the development of gifted students’ conceptual knowledge and the improvement of inquiry skills. A total of 43 sixth-grade gifted students were the participants. Whereas there were 22 students in the control group, in which hands-on experimentation was followed, 21 sixth-grade students were involved in the experimental condition, where virtual laboratory environments were used. Two different data-gathering tools, a multiple-choice conceptual knowledge test and inquiry skills test, were used in this study. The results revealed that although both groups enhanced their conceptual knowledge and improved their inquiry skills throughout the study, the students in the experimental group reached significantly higher scores than their counterparts for both of the tests. Several suggestions were done for both science teachers and researchers concerning the outcomes of the current study.